Efektifitas Media Poster Terhadap Peningkatan Pengetahuan dan Sikap Ibu Tentang Peran Caregiver Dalam Pencegahan Stunting Pada Balita di Puskesmas Sui. Asam - Daevi Khairunisa; Melly Nirma Syahriani; Nurhasanah Nurhasanah; Yetty Yuniarty (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting conditions in toddlers indicate growth disorders that can be indicated by abnormal height due to chronic nutritional deficiencies. One of the impacts of stunting is delayed brain development and the risk of low immunity, which affects productivity in toddlers and adults. Mothers as caregivers, namely people who are responsible for caring for and meeting the needs of children, especially stunting, must be given Health Education in order to prevent the incidence of stunting in their toddlers. The purpose of this study was to analyze the effectiveness of providing health education through poster media on increasing mothers' knowledge and attitudes about the role of caregivers in the risk of preventing stunting in toddlers. This research method is a quasi-experimental pretest and posttest. The location of this research was at the Sungai Asam Health Center, Kubu Raya Regency. The sample obtained from total sampling amounted to 30 subjects. Data collection techniques using questionnaires about maternal knowledge and attitudes. Data analysis using paired t-test. The results of the study are p value of 0.000, so it means that there is an effectiveness of poster media on increasing the knowledge and attitudes of mothers who act as caregivers in preventing stunting in toddlers. Poster media can increase mothers' knowledge and attitudes towards the risk of stunting prevention, the hope is that caregivers can pay attention to nutritional needs and parenting for children to prevent stunting. Keywords: Media, Health Education, Poster, Stunting, Caregiver